Legal Satisfaction for the Creditors to Obtain a Return of the Credit From the Debtor - Ahmad Fauzi (Budapest International Research and Critics University, 2020)
In the process of granting credit by the bank to the debtor, a careful analysis has been done, but in the implementation there are often many factors that can cause the debtor to become unable to repay the credit received. So as to guarantee repayment of credit given to the debtor, the bank asks for a guarantee from the debtor in the form of property or personal collateral. In accordance with the nature of the collateral, the collateral in the form of land and buildings is generally preferred by banks because the value tends to be stable in the long run. Thus, it is necessary to have a regulation governing the guarantee of assets in the form of land and buildings so that an ease and certainty is obtained for the bank in obtaining repayment of loans given to debtors if in the future the debtor is apparently unable to repay these obligations. It is necessary to create a strong guarantee institution and be able to provide legal certainty for all parties with an interest in providing credit by banks, the government has enacted and enforced it. to impose Mortgage Rights cannot be withdrawn or cannot be terminated by any reason except because it has been implemented or has expired. The provisions are intended so that the encumbrance of the Underwriting Right is actually implemented so as to provide legal certainty for the holder and the giver of the Underwriting Right.